Characteristic Analysis of Serum Vitamin D Levels with Hba1c in Type 2-Diabetes Mellitus Patients - Emma Novita; Mariana Mariana; Hana U; Alya Tsabita; Irma Yolanda; Syafira Yulia Sari (Sriwijaya Journal of Medicine, 2024)
Diabetes is one of the most rapidly growing global health emergencies of the 21st century, it is estimated that 537 million (10.3%) people have diabetes, and this number is expected to reach 643 million (11.3%) in 2030, and 783 million (12.2%) %) in 2045. Vitamin D plays a role in insulin secretion by stimulating beta-cell secretion or facilitating the conversion of pro-insulin to insulin. Therefore, vitamin D deficiency may be involved in the pathogenesis of DM type 2. This study aims to analyze the characteristics, HbA1c level status, and vitamin D level status in DM type 2 patients in primary care. The research was conducted in September 2022 with DM type 2 patients who came to the Plaju Palembang Health Center as research subjects. The results showed that there was a significant relationship between age and HbA1c levels in DM type 2 patients (p=0.020) and there was no relationship between gender, occupation, education level, BMI, abdominal circumference, family history, duration of diabetes, and vitamin D levels with HbA1c levels in DM type 2 patients (p>0.05)